Nanotechnologies in Food and Agriculture 2015
DOI: 10.1007/978-3-319-14024-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Nano-fertilizers and Their Smart Delivery System

Abstract: Outburst of world population in the past decade has forced the agricultural sector to increase crop productivity to satisfy the needs of billions of people especially in developing countries. Widespread existence of nutrient deficiency in soils has resulted in great economic loss for farmers and significant decreases in nutritional quality and overall quantity of grains for human beings and livestock. Use of large-scale application of chemical fertilizers to increase the crop productivity is not a suitable opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
126
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(170 citation statements)
references
References 66 publications
(60 reference statements)
2
126
0
1
Order By: Relevance
“…The excessive application of pesticides should be replaced by nanoemulsions, nanocomposites and nanoparticle formulations that are safe, effective and environmentally sustainable in the killing of agricultural pests and pathogens. The development of nanoformulations of agrochemicals for applying fertilisers (discussed in the next section) and pesticides is one aspect of the agriculture sector that is receiving increasing interest , …”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The excessive application of pesticides should be replaced by nanoemulsions, nanocomposites and nanoparticle formulations that are safe, effective and environmentally sustainable in the killing of agricultural pests and pathogens. The development of nanoformulations of agrochemicals for applying fertilisers (discussed in the next section) and pesticides is one aspect of the agriculture sector that is receiving increasing interest , …”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
“…However, there is a need for sufficient development in nanoencapsulation, in terms of cost–benefits and effectiveness to enhance the applications of nanoencapsulated pesticides. In recent laboratory‐scale experiments, it has been identified that modern nano‐fertilisers can improve agricultural yield by increasing the rate of seed germination, photosynthetic activity, seedling growth, nitrogen fixation, and carbohydrate–protein metabolism , …”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
See 3 more Smart Citations